2009
DOI: 10.4161/rna.6.4.9318
|View full text |Cite
|
Sign up to set email alerts
|

Role and mechanism of U1-independent pre-mRNA splicing in the regulation of alternative splicing

Abstract: In metazoan organisms, alternative splicing is a central mechanism for the regulation of gene expression. However, many questions remain about the underlying molecular mechanisms. Our recent work suggests that U1 snRNP-independent premRNA splicing occurs in humans, which contributes to the regulation of alternative splicing. So far it has been reported that several pre-mRNAs were spliced efficiently in a U1 snRNP-independent manner in vitro. Although the molecular mechanism and functional significance of U1-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
(29 reference statements)
1
6
0
Order By: Relevance
“…Although spliceosome assembly in human extracts is similarly blocked by degrading U2 snRNA(Krainer and Maniatis, 1985), human extracts supplemented with SR proteins are capable of splicing even in the absence of U1 snRNP(Crispino et al, 1994; Konforti et al, 1993; Tarn and Steitz, 1994). This difference between the yeast and mammalian systems likely reflects additional positive interactions in the mammalian system between the core splicing machinery and non-snRNP splicing factors bound to exonic and intronic splicing enhancer (ESE and ISE) elements (reviewed in (Fukumura and Inoue, 2009; Roca et al, 2013)).…”
Section: Discussionmentioning
confidence: 99%
“…Although spliceosome assembly in human extracts is similarly blocked by degrading U2 snRNA(Krainer and Maniatis, 1985), human extracts supplemented with SR proteins are capable of splicing even in the absence of U1 snRNP(Crispino et al, 1994; Konforti et al, 1993; Tarn and Steitz, 1994). This difference between the yeast and mammalian systems likely reflects additional positive interactions in the mammalian system between the core splicing machinery and non-snRNP splicing factors bound to exonic and intronic splicing enhancer (ESE and ISE) elements (reviewed in (Fukumura and Inoue, 2009; Roca et al, 2013)).…”
Section: Discussionmentioning
confidence: 99%
“…Similar cross-exon regulation of intron excision has been reported for alternative splicing regulation of exon 9 of the human ATP5C1 gene encoding mitochondrial ATP synthase γ subunit, where RBFOX1 represses excision of intron 9 by binding to GCAUG stretches in intron 8 to interfere with E complex formation on intron 9 (58). Interestingly, ATP5C1 intron 9 has been shown to be excised by U1-independent U2-type splicing which contributes to alternative splicing regulation although the molecular mechanism is to be elucidated (59,60). Genome-wide analysis of PTBP1–RNA interactions suggested that binding of PTBP1 near the constitutive 3′-splice site of the downstream introns interferes with the recognition of the constitutive 3′-splice site to promote the use of the alternative exons (61).…”
Section: Discussionmentioning
confidence: 99%
“…U1-independent splicing may be an example that supports this explanation [47,48]. Although the detailed mechanism of U1-independent splicing is unclear and further research is needed, hF1γ intron 9, whose 5' splice site sequences are different from the consensus sequence at positions -3 and +5, spliced out without U1 snRNP.…”
Section: Discussionmentioning
confidence: 99%